Revitalization of mosque functions in society empowerment (Case study of Suciati Saliman Mosque, Yogyakarta) - Mauliya Redyan Nurjannah; Dewi Eka Wulandari; Latifur Rohmah (Proceeding International Conference on Accounting and Finance, 2024)
Back to Masjid became a great encouragement for Muslims to pay attention to the function of mosques universally. In the time of the Prophet SAW the mosque was used as the center of civilization. So how in this modern era we both strive to restore the function of the mosque, not only as a place of worship. However, it can also function as a place to improve community welfare through various productive activities. Masjid Suciari Saliman is a mosque located in Sleman regency and has several community empowerment programs that need to be emulated by other mosques. This research uses qualitative descriptive method with case studies. Empowerment in the Suciati Saliman Mosque is carried out through three divisions formed including: the Prosperity of the Mosque, Educational Institutions, and Social Institutions and Economic Empowerment.